Personel Working with Disabled Children in Special Education Institutions First Aid Information and Practices - Dertli, Semiha; Başdaş, Öznur (Necmettin Erbakan Üniversitesi, 2022)
Purpose: This research was carried out as a descriptive study in order to determine the first aid knowledge level of personnel working with disabled children in special education institutions and the factors affecting their knowledge levels. Method: This research was conducted with 145 personnel working in special education and rehabilitation centers affiliated to the Directorate of National Education in a province in the east of Turkey and volunteering to participate in the research. “Introductory Information Form” and “Basic First Aid Practices Questionnaire” were used to collect data. Descriptive statistics, Mann Whitney U and Kruskal Wallis tests were used in the analysis of the data. Results: It was determined that the average age of the personnel participating in the research was 29.41±7.08 years, 66.2% were women and 84.1% were undergraduate graduates. It was found that the tenure of the personnel in the institution was 4.19±3.85 years and 66.2% of them worked as teachers. It was determined that 85.5% of the personnel working in the institutions received first aid training, and 53.1% of the trainees received this training from the school they graduated from. It was stated that 49.0% of the participants rarely encountered events that required first aid in the institution; It was determined that 62.1% of them evaluated their first aid knowledge as moderate and the Basic First Aid Practices Questionnaire average score was 14.22±2.66. It has been found that the most common types of accidents encountered by personnel working with disabled children in special education institutions are falling-hit and fainting-seizure. Conclusion and Suggestions: In the study, it was determined that the average score of the Basic First Aid Practices Questionnaire of the personnel working in the institution was high. It was determined that the average score of the personnel who received training and evaluated the first aid education level as good, was higher and the difference between the groups was statistically significant. In line with these results, it is thought that a child's life can be saved or lifelong disabilities can be prevented by applying regular, up-to-date and qualified training programs to the personnel working in private education institutions.

Amaç: Bu araştırma, özel eğitim kurumlarında engelli çocuklar ile çalışan personellerin ilk yardım bilgi düzeyleri ile bilgi düzeylerini etkileyen faktörleri belirlemek amacıyla tanımlayıcı olarak yapılmıştır. Gereç -Yöntem: Bu araştırma, Türkiye’nin doğusunda bir ilde Milli Eğitim Müdürlüğüne bağlı özel eğitim ve rehabilitasyon merkezlerinde çalışan ve araştırmaya katılmaya gönüllü olan 145 personel ile yapılmıştır. Verilerin toplanmasında “Tanıtıcı Bilgi Formu” ve “Temel İlk Yardım Uygulamaları Anketi” kullanılmıştır. Verilerin analizinde tanımlayıcı istatitikler, Mann Whitney U ve Kruskal Wallis testleri kullanılmıştır. Bulgular: Araştırmaya katılan personelin yaş ortalamasının 29.41±7.08 yıl, %66.2’sinin kadın ve %84.1’inin lisans mezunu olduğu belirlenmiştir. Personelin kurumdaki görev süresinin 4.19±3.85 yıl olduğu ve %66.2’sinin öğretmen olarak çalıştığı bulunmuştur. Kurumlarda çalışan personellerden %85.5’inin ilk yardım eğitimi aldığı, eğitim alanların %53.1’inin ise bu eğitimi mezun olduğu okuldan aldığı saptanmıştır. Çalışmaya katılanların %49.0’ının kurumda ilk yardım gerektirecek olaylar ile nadiren karşılaştığı; %62.1’inin ilk yardım bilgisini orta düzeyde olarak değerlendirdiği ve Temel İlk Yardım Uygulamaları Anketi puan ortalamasının 14.22±2.66 olduğu belirlenmiştir. Özel eğitim kurumlarında engelli çocuklar ile çalışan personelin en sık karşılaştığı kaza türlerinin düşme-çarpma ve bayılma-nöbet olduğu bulunmuştur. Sonuç–Öneriler: Araştırmada kurumda çalışan personelin Temel İlk Yardım Uygulamaları Anketi puan ortalamasının yüksek olduğu belirlenmiştir. Eğitim alan ve ilk yardım eğitim düzeyini iyi olarak değerlendiren personelin puan ortalamasının daha yüksek ve gruplar arasındaki farkın istatistiksel olarak önemli olduğu belirlenmiştir. Bu sonuçlar doğrultusunda özel eğitim kurumlarında çalışan personele düzenli, güncel ve nitelikli eğitim programlarının uygulanması ile bir çocuğun hayatının kurtarılabileceği veya ömür boyu sürebilecek sakatlıkların önüne geçilebileceği düşünülmektedir.
Engeli Olan Çocuklar ile Çalışan Personelin İlk Yardım Bilgi ve Uygulamaları
Keywords: Health Care Administration; Sağlık Kurumları Yönetimi